1978
DOI: 10.1177/003072707800900504
|View full text |Cite
|
Sign up to set email alerts
|

Conserving grain on the small farm in the tropics

Abstract: Traditionally, structures for the storage of grain from peasant farms in tropical countries have been concerned with keeping the rain off, and the rats out. However, a major source of loss in storage, that caused by insect damage, has not been effectively controlled by traditional methods. The use of fumigants, certain safe and effective insecticides, and improvements to storage structures may provide a solution, but the existence of an adequate and well-trained advisory service is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Subsistence agriculture requires that the farmer store a percentage of staple food to feed his family and livestock between harvests (Hindmarsh et al, 1978). Giles (1964) has suggested that the largest quantity of food in the tropics is stored in the traditional farmer's small granaries.…”
Section: Introductionmentioning
confidence: 99%
“…Subsistence agriculture requires that the farmer store a percentage of staple food to feed his family and livestock between harvests (Hindmarsh et al, 1978). Giles (1964) has suggested that the largest quantity of food in the tropics is stored in the traditional farmer's small granaries.…”
Section: Introductionmentioning
confidence: 99%
“…It prefers to feed and develop on cowpea (Vigna unguiculata (L.) Walp), but it is also known to feed on other legume seeds (Applebaum et al 1970). Subsistence agriculture requires that the farmer store a percentage of staple food to feed his family and livestock between harvests (Hindmarsh et al 1978). The largest quantity of food in the tropics is stored in traditional farmer's granaries and in most cases under one roof (Lambert et al 1985;Stathers et al 2002).…”
mentioning
confidence: 99%
“…The pyrethroids used were beta cyfluthrin, 12.5%; deltamethrin, 2.5%; and alpha cypermethrin, 10% at doses of 0.250 and 0.125 ppm each. The main criterion for selecting these insecticides was their low mammalian toxicity (Hindmarsh et al, 1978). All formulations used were emulsifiable concentrates (EC).…”
Section: Methodsmentioning
confidence: 99%